Enabling Support of Collaborative Cross-enterprise Business Processes for Legacy ERP Systems - Gundars Alksnis; Ērika Asņina; Mārīte Kirikova; Egils Meiers (Complex Systems Informatics and Modeling Quarterly)
In order to create innovative business products, share knowledge between people and businesses, or increase the control and quality of services, more and more often enterprise business processes involve in collaborations by delegating or providing some pieces of work to other enterprises. Necessity to cooperate in the cross-enterprise setting leads to Collaborative Business Processes (CBPs). The difference between CBPs and Business Processes (BPs) is in the decentralized coordination, flexible backward recovery, participants notification about the state, efficient adaptability to changes, presence of multiple information systems, and individual authorization settings. In the paper we consider a specific case of CBPs where multiple collaborating partners use Enterprise Resource Planning (ERP) system of the same vendor. The vendor can see (e.g., monitor) the changes of data elements, but does not have explicit process awareness in the ERP system to support flow of activities in the cross-enterprise setting. The paper also discusses different settings of cross-enterprise CBP and shows simplified enterprise models behind the vendor possibilities to positively impact collaborative processes. The restrictions of the vendor are implicit information flows in BP, diversity of ERP integrations with third party Information Systems (IS), the lack of mechanisms for monitoring BP instances, backward recovery, user notification about the current state and tasks, and inability to make explicit changes in customers’ ISs.